Characterization of the complete mitochondrial genome of the black Alpaca breed of Vicugna pacos (Mammalia, Artiodactyla, Camelidae) from Puno, Peru - Danilo E. Bustamante; Claudia Esther Yalta-Macedo; Juancarlos Alejandro Cruz; Jorge Luis Maicelo-Quintana; Juan Carlos Guerrero-Abad; Dina Lida Gutierrez-Reynoso (Mitochondrial DNA. Part B. Resources, 2020)
The domestic South American camelid Vicugna pacos L. is distributed along Peru, Chile, Bolivia, and Argentina. Here, we contribute to the bioinformatics and evolutionary systematics of the Camelidae by performing high-throughput sequencing analysis on the black Huacaya breed of V. pacos from Puno, Peru. The black Huacaya breed mitogenome is 16,664 base pairs (bp) in length and contains 37 genes (GenBank accession MT044302). The mitogenome shares a high-level of gene synteny to other Camelidae (Camelops, Camelus, Lama, and Vicugna). The mitogenome of the black Huacaya breed of V. pacos situates it in a clade with V. vicugna Molina, sister to Lama. We anticipate that further mitogenome sequencing of different breeds from Vicugna pacos will improve our understanding of the evolutionary history of this taxon.